Divergent Anabolic Signalling responses of Murine Soleus and Tibialis Anterior Muscles to Chronic 2G Hypergravity - Timur Mirzoev (Nature Portfolio, 2017)
Abstract The purpose of the study was to assess the rate of protein synthesis (PS) and elucidate signalling pathways regulating PS in mouse soleus (Sol) and tibialis anterior (TA) muscles following chronic hypergravity (30-day centrifugation at 2G). The content of the key signalling proteins of the various anabolic signalling pathways was determined by Western-blotting. The rate of PS was assessed using in-vivo SUnSET technique. An exposure to 2G centrifugation did not induce any significant changes in the rate of PS as well as phosphorylation status of the key anabolic markers (AKT, p70s6k, 4E-BP1, GSK-3beta, eEF2) in Sol. On the contrary, a significant 55% increase in PS (p < 0.05) was found in TA. The cause of such a rise in PS could be associated with an increase in AKT (+72%, p < 0.05), GSK-3beta (+60%, p < 0.05) and p70s6k (+40%, p < 0.05) phosphorylation, as well as a decrease in eEF2 phosphorylation (−46%, p < 0.05) as compared to control values. Thus, the results of our study indicate that 30-day 2G centrifugation induces a distinct anabolic response in mouse Sol and TA muscles. The activation of the PS rate in TA could be linked to an up-regulation of both mTORC1-dependent and mTORC1-independent signalling pathways.